Branch Level Courier Employee Performance Measurement Using the Human Resource Scorecard and Analytical Hierarchy Process: Evidence from a Bangkok Logistics Branch - Kanyarat Phasukchai; Chalita Boonmee; Suphaporn Minambue (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
This study evaluates courier employee performance at a Bangkok branch of a Thai logistics company by integrating the Human Resource Scorecard (HRSC) and the Analytical Hierarchy Process (AHP). The study is designed as a descriptive evaluative case study rather than a causal test of company wide organizational performance. Employee data were obtained from 40 active couriers through a structured questionnaire and operational performance records, while priority judgments were obtained from three managerial experts who were directly involved in branch human resource and courier operations. The HRSC framework was used to classify performance indicators into financial, customer, internal business process, and learning and growth perspectives. AHP was used to assign relative managerial priority weights through pairwise comparison, not to test statistical influence. After correcting the normalization of the reported priority vector, learning and growth received the highest priority, followed by financial, customer, and internal business process perspectives. Performance achievement was then evaluated by combining capped achievement scores with global AHP weights. The measurable KPI composite score was 96.16, indicating green branch level performance based on the revised threshold of Green >= 90, Yellow >= 70 and < 90, and Red < 70. The findings suggest that learning, digital capability, career development, attendance discipline, service reliability, and internal communication should be treated as managerial priorities for branch improvement. The results are limited to the selected branch, cross sectional observations, a small expert panel, and self reported employee measures. Therefore, broader relevance to logistics firms in Thailand or ASEAN should be interpreted cautiously and requires external validation.